2010
DOI: 10.1051/forest/2009110
|View full text |Cite
|
Sign up to set email alerts
|

Diversité fonctionnelle et processus écosystémiques dans des assemblages synthétiques d’espèces d’arbres de forêt tropicale

Abstract: Abstract• The elucidation of relationships between biodiversity and ecosystem processes has been limited by the definition of metrics of biodiversity and their integration into experimental design. Functional trait screening can strengthen the performance of these designs.• We suggest the use of Rao's quadratic entropy to measure both functional diversity and phylogenetic diversity of species mixtures proposed for an experimental design, and demonstrate how they can provide complementary information.• We also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Tree species richness might better reflect functional trait diversity than the tree type richness used in our study. Biodiversity categories based on growth forms are “soft traits” that may mask within-group variability of traits [51]. Recent studies have shown that functional diversity indices based on traits relating to reproduction, growth, successional status and resource use perform better than indices of species diversity [13], [52].…”
Section: Discussionmentioning
confidence: 99%
“…Tree species richness might better reflect functional trait diversity than the tree type richness used in our study. Biodiversity categories based on growth forms are “soft traits” that may mask within-group variability of traits [51]. Recent studies have shown that functional diversity indices based on traits relating to reproduction, growth, successional status and resource use perform better than indices of species diversity [13], [52].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may be focused on the toleration limits to environmental variation within species of different successional status. Research in this topic may contribute to develop theoretical approaches on species functional roles in forest ecosystems (niche vs. neutral theories, Hubbell 2005) that could be applied in silvicultural and ecological restoration (Baraloto et al 2010; Park et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The three late‐successional species ( Brosimum alicastrum , Ampelocera hottlei , and Dalium guianense ) displayed poor seedling survival at both the study sites,however, should not be discarded or neglected definitely. In view of their slow growth and shade tolerance (Paz 2003), these species can be used in enrichment plantings as a means to establish additional species in a secondary forest or tree plantation (Butterfield 1995; Baraloto et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Species with a fast-growing strategy should show high values of specific leaf area (Poorter and Bongers, 2006), but we observed the opposite. Nevertheless, it has been suggested that stem and leaf traits are not coordinated (Baraloto et al, 2010), indicating that the lower values of SLA may represent a phenotypic acclimation to high levels of light availability (Poorter, 2001). Additionally, each functional trait can reveal different mechanisms that drive forest regeneration (Lasky et al, 2014a).…”
Section: Functional Traits and Canopy Opennessmentioning
confidence: 99%